Effects of Salinity on Distribution of Alien Invasive and Indigenous Byssally-attached Bivalves in the Songkhla Lake Basin - Nattacha Khanthasimachalerm (Prince of Songkla University, 2024)
Master of Science in Biology (International Program), 2023